Outcome of Acute Kidney Injury (AKI) Patients in the Intensive Care Unit of Enam Medical College & Hospital During the Period of July 2018 to May 2019 (Journal of Enam Medical College, 2023)
Background: Acute kidney injury (AKI) is a public health issue associated with multiple clinical conditions which may occur due to slight elevation in serum creatinine to anuric renal failure with electrolytes and acid-base imbalance, chronic kidney diseases, end-stage renal diseases, impaired innate immunity associated with higher infection rate, and increased duration of hospital stay with higher cost. Sometimes severe AKI patients may need intensive care support and renal replacement therapy. Severe sepsis is the most common cause of ICU admission.Materials and Methods: This observational study was conducted during the period of July 2018 to May 2019 in the Department of Anesthesiology and Intensive Care Unit of Enam Medical College & Hospital, Savar Dhaka. A total of 87 AKI patients were selected among which 48 were male and 39 were female. Acute kidney injury was selected with an increase in serum creatinine >0.3 mg /dL within 48 hours or ≥1.5 mg /dL from the base line within prior 7 days or urine volume